Isolasi Jamur Endofit dari Sonneratia Alba dan Toksisitasnya Terhadap Artemia Salina - Mairing, Priskila Putri (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Endophytic fungi are microorganisms that live in plant tissues asymptomatically. Endophytic fungi can produce secondary metabolites with various biological activities, one of which is anticancer. Mangroves are known to be a potential source of endophytic fungi that have active secondary metabolites. One of the dominant species of mangrove is perepat (Sonneratia alba). This study aims to isolate endophytic fungi, isolate and identify endophytic fungi from adhesives (S. alba), as well as toxicity test using the BSLT method on Artemia salina shrimp larvae. The study began with the isolation and purification of endophytic fungi, macroscopic and microscopic identification, cultivation and extraction, and toxicity test using the Brine Shrimp Lethality Test method. The isolation results of the leaf endophytic fungus S. alba were isolate SA-L1-1 which after being identified macroscopically and microscopically had similar characteristics with Nigrospora sp. In the toxicity test, the endophytic fungal isolate extract SA-L1-1 was toxic to A. salina shrimp larvae with an LC50 of 405.109 ppm.